Managing uncertainty: Principles for improved decision making. (2020) - Kaye, P. H.; Smith, A. D.; Strudwick, M. J.; White, M.; Bird, C. E. L.; Aggarwal, G.; Durkin, T.; Marcuson, T. A. G.; Masters, T. R.; Regan, N.; Restrepo, S.; Toller, J. R.; et al.
Abstract: Effective management of uncertainty can lead to better, more informed decisions. However, many decision makers and their advisers do not always face up to uncertainty, in part because there is little constructive guidance or tools available to help. This paper outlines six Uncertainty Principles to manage uncertainty. Face up to uncertainty Deconstruct the problem Don't be fooled (un/intentional biases) Models can be helpful, but also dangerous Think about adaptability and resilience Bring people with you These were arrived at following extensive discussions and literature reviews over a 5-year period. While this is an important topic for actuaries, the intended audience is any decision maker or advisor in any sector (public or private).